KD Pomboboros : An Interactive Language Learning Mobile Application Using Augmented Reality And Virtual Reality - Errickson, Effin Guta (2021)
KD Pomboboros is a mobile application developed by using a combination of Virtual Reality and Augmented Reality. The idea of KD Pomboboros came into realization because of the declining rate of native Dusun language speaker. KadazanDusun is the largest indigenous ethnic group in Sabah with 17.8% out of 3.2 million population. Although they are the largest ethnic group in Sabah, the number of people who can speak or write in their mother tongue is declining. In an earlier 2005 UNESCO’s report, the KadazanDusun language was classified as an endangered language, spoken by a mere 300000 people only. The language has apparently joined about 7000 other languages worldwide that face the real threat of extinction. Prior to the formation of Malaysia in 1963, the KadazanDusun language was the predominant languages in all KadazanDusun households. After 1963, Malay gradually replaced English as the medium of instruction in schools, and the official language in government. Sabah Malay, which according to a study, is a dialect of Malay rather than a bazaar language, has become the language of communication among the multi-ethnic groups in Sabah. Through constant and popular use, Sabah Malay gradually replaced the original language in KadazanDusun homes. This language shift contributed to the decline in the use of the KadazanDusun Language. The current speakers of KadazanDusun language are mostly in the fifty-year old and above category. Thus an aggressive approach must be taken to preserve the native language from becoming extinct. Therefore, the mobile app aims to improve the ability to learn Dusun language process and to attract the Dusun people to learn their native language. Integrating mixed reality (Augmented Reality (AR) and Virtual reality (VR)) technology into the app has a positive impact on user learning and engagement. By having this application, it is expected that there would be a growing number of Dusun native speakers.